A Case Study on Students’ Perceptions of Project-Based Learning in Teaching Writing at a Senior High School - Syafwa, Renindi Putri; Srisudarso, Mansyur; Abas , Totoh Tauhidin (Journal of Educational Sciences, 2025)
This study explores students’ perceptions of Project-Based Learning (PjBL) in teaching writing at an Islamic and science-based senior high school in East Jakarta. The research was conducted to understand how students viewed PjBL as an alternative method that could make writing more engaging and meaningful. A qualitative approach was used with six tenth-grade students selected based on different English proficiency levels. The data were collected through classroom observation, interviews, and supporting documents such as lesson plans and students’ writing projects. The findings showed that students generally had positive perceptions toward the use of PjBL in writing. They stated that this method made them feel more motivated and confident in expressing their ideas. Working in groups helped them share opinions, discuss topics, and improve their vocabulary and grammar through peer feedback. The opportunity to choose their own topic also made writing feel more enjoyable and personal. However, some students faced challenges in group work, such as unequal contribution and time management. Despite these challenges, they agreed that the teacher’s guidance and feedback were helpful during the process. In conclusion, PjBL created a more active, collaborative, and supportive writing environment that encouraged students to be more involved and independent in learning. It contributes to the growing body of literature by offering student-centered insights into how PjBL enhances writing experiences in Indonesian EFL classrooms.